Topical issues of the formation of an effective economic and social policy in Cambodia - S. Liv; I. V. Tregub; А. S. Fedyunin (Управленческие науки)
Cambodia, currently classified as a lower-middle-income developing country, aspires to reach upper-middle-income status by 2030. To achieve this ambitious goal, the Cambodian government has embraced an open market economic system and prioritized attracting foreign investments as well as encouraging final consumption expenditure (FCE) and stimulating the level of industries, including construction. This study aims to find out the influences of the fluctuations of foreign direct investment (FDI), FCE, and industry (including construction) (IIC) on gross domestic product (GDP) growth in Cambodia and to identify the key factors that can increase FDI, FCE, and IIC growth. The study employs descriptive and correlational analysis, mainly focusing on statistical analyses by constructing an econometric model. The results indicate that Cambodia’s GDP is directly and positively impacted by the FDI, FCE, and IIC, according to the analysis of the specification of the econometric model using a linear mathematical equation. The study concludes that the Cambodian government’s attention to strategic policies and initiatives in promoting FDI, FCE, and IIC, ultimately leading to a higher overall economic growth rate, is crucial. Factors such as political stability and governance, regulation and legal framework, infrastructure, human capital development, market access, publicprivate partnership, fiscal policy, and social protection should be at the forefront of the Cambodian GDP development roadmap.